Long Term Crop-Livestock Managements on Physical Soil Attributes and Total Organic Carbon - Possamai, Edivan José; Conceição, Paulo Cesar; Stumpf, Lizete; Paier, Cristiane Dalagua; Rosa, Jaqueline Kristiane da; Adami, Paulo Fernando (Journal of Agricultural Studies, 2021)
Crop-livestock system (CLS) based on summer crops, as soybean and corn, in rotation with oat+ryegrass pasture in winter for dairy products, is the most adopted productive system at the southern region of Paraná, Brazil. Although its management needs to be evaluated, in order to improve its sustainability. In this sense, this study aimed to measure the impacts of management practices of five smallholder farms on soil quality, considering the soil use history. Soil samples were collected to determine soil bulk density (BD), macroporosity (Ma), microporosity (Mi), weighted mean diameter (WMD) in each area under CLS, summer pasture and native forest, as a control. Areas under CLS altered soil physical attributes (higher BD and Mi and lower Ma) in relation to the non-anthropized area as a consequence of animal trampling. However, the conservationist management adopted, with the soil cover maintenance along with years of minimum tillage, the use of grasses with aggressive roots along with the winter period, did not culminate in limitations of soil functions. Soil structure dynamics needs to be investigated to better determine the biological and physical influence on the formation of soil aggregation.